Centrality-Dependent Modification of Jet-Production Rates in Deuteron-Gold Collisions at √[s(NN)]=200 GeV - Adare, A; Aidala, C; Ajitanand, N N; Akiba, Y; Al-Bataineh, H; Alexander, J; Alfred, M; Angerami, A; Aoki, K; Apadula, N; Aramaki, Y; Asano, H; et al. (Physical review letters, 2016)
Jet production rates are measured in p+p and d+Au collisions at sqrt[s_{NN}]=200 GeV recorded in 2008 with the PHENIX detector at the Relativistic Heavy Ion Collider. Jets are reconstructed using the R=0.3 anti-k_{t} algorithm from energy deposits in the electromagnetic calorimeter and charged tracks in multiwire proportional chambers, and the jet transverse momentum (p_{T}) spectra are corrected for the detector response. Spectra are reported for jets with 12<p_{T}<50 GeV/c, within a pseudorapidity acceptance of |η|<0.3. The nuclear-modification factor (R_{dAu}) values for 0%-100% d+Au events are found to be consistent with unity, constraining the role of initial state effects on jet production. However, the centrality-selected R_{dAu} values and central-to-peripheral ratios (R_{CP}) show large, p_{T}-dependent deviations from unity, challenging the conventional models that relate hard-process rates and soft-particle production in collisions involving nuclei.